2016
DOI: 10.1155/2016/6138251
|View full text |Cite
|
Sign up to set email alerts
|

RPRep: A Robust and Privacy-Preserving Reputation Management Scheme for Pseudonym-Enabled VANETs

Abstract: Establishing trust and reputation for evaluation of message reliability is key to the vehicular ad hoc networks (VANETs). Most of the previous reputation management systems focus on the effectiveness of the reputation management system in handling the liars who send false service messages. However, these reputation management systems have two drawbacks. One is that they are vulnerable to tactical attacks such as self-promoting attacks and bad-mouthing attacks. The other is that they may violate location privac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…After that, the trust value method for compositing different assumptions is explained in the same section. The proposed method for multiple vehicles trusted management is presented in the third subsection …”
Section: Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, the trust value method for compositing different assumptions is explained in the same section. The proposed method for multiple vehicles trusted management is presented in the third subsection …”
Section: Proposed Methodsmentioning
confidence: 99%
“…The proposed method for multiple vehicles trusted management is presented in the third subsection. 56,57 In this proposed method, we designed protocol, and our assumption is that there is a unique ID (identity information) for each vehicle in the road network. All vehicles ID register with RS first.…”
Section: Dynamic Pseudonym Trust Management Partmentioning
confidence: 99%
“…In particular, the attack can be directed to a specific victim, trying to reconstruct its habits or its driving path by analyzing its beacons, or it can be directed to the entire driver community, studying large-scale patterns to predict its behavior. The key to solving this problem is decoupling the ID from the vehicle, which can be achieved by using a pseudonym system [46] that assigns the user a temporary ID and switches it under certain conditions. The conditions required by this strategy are perfectly suited to a parking area: the ID can be randomly switched among a set of cars that wait in a small geographical area for some time.…”
Section: Improving Vanets Security Using Sdn Paradigmmentioning
confidence: 99%
“…Wang et al [25] suggested the use of two servers. One of the servers issues pseudonyms and the other server checks the reputation of vehicles.…”
Section: Introductionmentioning
confidence: 99%